Journal of Digital Management - Wei, Jiang; Xie, Xiaoyun; Shen, Zuo-Jun Max.; Huo, Baofeng; Ahlstrom, David; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Journal of Digital Management is an Open Access journal which aims to publish original research articles and reviews on the digitalization of management, how digital technologies influence various management fields, including strategy, entrepreneurship, innovation management, operations and supply chain management, organization management, information management, and marketing. The journal will specifically encourage submissions that develop new theories in management that can explain emerging organizational practices in the digital environment.
Keywords: Business; Management science; Business and Management